Developing the Neurology Diversity Officer: A Roadmap for Academic Neurology Departments. (23rd February 2021) - Mohile, Nimish A.; Spector, Andrew R.; Ebong, Ima M.; Flippen, Charles; Gutierrez, Camilo; Leacock, Rodney O.; Marulanda-Londoño, Erika; Mejia, Nicte I.; Thomas, Reena; Hamilton, Roy H.
Abstract : Academic neurology departments must confront the challenges of developing a diverse workforce, reducing inequity and discrimination within academia, and providing neurologic care for an increasingly diverse society. A neurology diversity officer should have a specific role and associated title within a neurology department as well as a mandate to focus their efforts on issues of equity, diversity, and inclusion that affect staff, trainees, and faculty. This role is expansive and works across departmental missions, but it has many challenges related to structural intolerance and cultural gaps. In this review, we describe the many challenges that diversity officers face and how they might confront them. We delineate the role and duties of the neurology diversity officer and provide a guide to departmental leaders on how to assess qualifications and evaluate progress. Finally, we describe the elements necessary for success. A neurology diversity officer should have the financial, administrative, and emotional support of leadership in order for them to carry out their mission and to truly have a positive influence.